2005
DOI: 10.1161/01.res.0000173298.38808.27
|View full text |Cite
|
Sign up to set email alerts
|

Pre–B-Cell Colony–Enhancing Factor Regulates NAD + -Dependent Protein Deacetylase Activity and Promotes Vascular Smooth Muscle Cell Maturation

Abstract: Abstract-Conversion of vascular smooth muscle cells (SMCs) from a proliferative state to a nonproliferative, contractile state confers vasomotor function to developing and remodeling blood vessels. Using a maturation-competent human SMC line, we determined that this shift in phenotype was accompanied by upregulation of pre-B-cell colony-enhancing factor (PBEF), a protein proposed to be a cytokine. Knockdown of endogenous PBEF increased SMC apoptosis and reduced the capacity of synthetic SMCs to mature to a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
152
2
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(160 citation statements)
references
References 31 publications
2
152
2
4
Order By: Relevance
“…PBEF mimics insulin signaling by binding to the insulin receptor with an affinity similar to that of insulin but does not share the binding site with insulin on the insulin receptor. In contrast, previous studies have shown intracellular expression of PBEF and have demonstrated that PBEF is a nicotinamide phosphoribosyltransferase (7,8). Overexpression of PBEF in human vascular SMCs induced enhanced survival by its regulatory effect on NADdependent deacetylase activity.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…PBEF mimics insulin signaling by binding to the insulin receptor with an affinity similar to that of insulin but does not share the binding site with insulin on the insulin receptor. In contrast, previous studies have shown intracellular expression of PBEF and have demonstrated that PBEF is a nicotinamide phosphoribosyltransferase (7,8). Overexpression of PBEF in human vascular SMCs induced enhanced survival by its regulatory effect on NADdependent deacetylase activity.…”
Section: Discussioncontrasting
confidence: 59%
“…Later, it became evident that PBEF is a multifunctional protein, having nicotinamide phosphoribosyltransferase, adipokine, and cytokine activities. In smooth muscle cells (SMCs), intracellularly located PBEF regulates NADϩ-dependent reactions and promotes the acquisition of a mature SMC phenotype (7,8). Fukuhara et al reported the expression of PBEF in visceral fat adipocytes and noted that its insulin-like effect is dependent on binding to the insulin receptor (9).…”
mentioning
confidence: 99%
“…Indeed, visfatin has been described to extend the life span of smooth muscle cells, via augmenting SIRT1-mediated p53 degradation (24,25). Furthermore, visfatin, in a NAD-dependent fashion, promotes the acquisition of a mature smooth Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have suggested that visfatin may also function analogous to a visceral fat adipocytokine and may alter insulin and glucose signaling, although this remains controversial (5). Evidence is accumulating to suggest that visfatin may serve as a cellular survival factor and may exert beneficial effects on both endothelial (8) and vascular smooth muscle cells (25). Indeed, in vascular smooth muscle cells, visfatin functions as a longevity protein, in part via optimizing Sirt1-mediated p53 degradation, whereas, in endothelial cells, visfatin may stimulate angiogenesis and augment endothelial survival (24).…”
mentioning
confidence: 99%
“…[55]. A similar direct relationship between Nampt, intracellular NAD levels and SIRT1 activity has been recently confirmed in several cell types including skeletal myoblasts [56], vascular smooth muscle cells [7], [57], and chondrocytes [58]. Of interest, the nuclear form of Nicotinamide…”
Section: Modulation Of Sirtuin Activity Through Nad Metabolismmentioning
confidence: 61%